Cervical intervertebral disc disease in 60 Yorkshire terriers - Palus, Viktor; Stehlik, Ladislav; Necas, Alois; Srnec, Robert; Urbanova, Lucie; Lu, Diane (Frontiers in Veterinary Science, 2023)
Intervertebral disc extrusion (IVDE) is a common neurological condition in many dog breeds. This study aimed to describe this condition in Yorkshire Terriers (YT) and calculate the prevalence of this condition amongst the YTs with neurological diseases. This is a double-centre retrospective study which was conducted in two arms. The first part of the study, describing the characteristics of cervical (C) IVDE in YTs, is based on data from 2005 to 2021. The second part of the study calculated the prevalence of C IVDE amongst the YTs with neurological diseases based on data from 2016 to 2021. A retrospective search through the medical records was conducted. YTs with C IVDE diagnosed with MRI and confirmed surgically were eligible for inclusion in this study. Sixty YTs were included in the first part of the study. There were 48 (80%) dogs with acute onset and 12 (20%) with chronic onset with acute deterioration. Ambulation was preserved in 31 (51.7%) dogs on admission, and the remaining 29 (48.3%) dogs were non-ambulatory. No significant association was found between ambulation on admission and recovery status (p = 0.547). Seventy-three intervertebral spaces were treated during the surgical intervention. Relapses were seen in seven (11.7%) dogs. Forty-nine (81.7%) dogs were ambulatory at discharge. A complete recovery was observed in 46 (76.7%) dogs; the remaining dogs (14, 23.3%) were classified as incomplete recovery. A significant difference was found in time to ambulation (p = 0.0238) and time to discharge (p = 0.0139) between the on-admission ambulatory and non-ambulatory dogs. Three hundred and eight YTs were diagnosed with neurological diseases between 2016 and 2021 in one referral centre. C IVDE was diagnosed in 31 (10.06%) dogs. This is the first study specifically describing the C IVDE in YTs and establishing the prevalence of this condition amongst YTs with other neurological disorders.